Well-controlled vs poorly-controlled diabetes in patients with COVID-19: Are there any differences in outcomes and imaging findings?. (August 2020) - Raoufi, Masoomeh; Khalili, Shayesteh; Mansouri, Mohsen; Mahdavi, Ali; Khalili, Neda
Abstract: Aims: We aimed to compare the clinical outcomes and imaging findings between COVID-19 patients with well-controlled diabetes and those with poorly-controlled diabetes. Methods: In this retrospective single-center study, 117 patients with coexistent COVID-19 and type 2 diabetes mellitus were included. Patients were divided into two groups based on HbA1c values. Clinical data and laboratory parameters were collected from patients' medical records. Also, the chest computed tomography (CT) score was defined by the summation of individual scores from 5 lung lobes: scores of 0, 1, 2, 3, 4 and 5 were respectively assigned for each lobe if pulmonary involvement was 0%, less than 5%, 5%-25%, 26%-49%, 50%-75%, or more than 75% of each region. Results: Among all patients with diabetes, 93 (79.5%) patients had poorly-controlled diabetes and 24 (20.5%) had well-controlled diabetes; 66 (56.4%) patients were male and the median age was 66 years (IQR, 55–75 years). The chest CT severity scores were not significantly different between patients with well-controlled diabetes and those with poorly-controlled diabetes (p = 0.33). Also, the mortality and recovery rates were similar between the two groups (p = 0.54 and p = 0.85, respectively). Conclusion: Based on the results, clinical outcomes and chest CT severity scores are similar between patients with well-controlled and poorly-controlled diabetes among the Iranian population with COVID-19.